Unlocking the therapeutic potential of bioactive compounds in Ganoderma lucidum: a new frontier in natural medicine - Khanal, Sonali; Thakur, Pratibha; Sharma, Aman; Kumar, Anand; Pillai, Manjusha; Kumar, Deepak; Kumar, Arun; Verma, Rachna; Tapwal, Ashwani; Kumar, Dinesh; Kumar, Vinod; Bala, Asis (3 Biotech, 2025)
Ganoderma lucidum (Reishi), a valued medicinal fungus used in traditional medicine for over 2000 years, has sparked widespread scientific attention due to its extensive range of bioactive ingredients and therapeutic promise in modern medicine. This study presents a detailed and up-to-date examination of G. lucidum's primary bioactive components, which include polysaccharides, triterpenoids, meroterpenoids, nucleotides, proteins, alkaloids, and sesquiterpenoids. These chemical components show a wide range of pharmacological effects, including immune modulation, cancer suppression, and neuroprotection. The review also gives insight on developing and underexplored therapeutic areas, such as the mushroom's antiviral properties particularly its anti-HIV potential as well as its anti-fibrotic, neuropharmacological, and anti-aging benefits. By combining traditional therapeutic knowledge with modern biomedical innovation, G. lucidum is positioned as a viable natural resource for solving modern health issues. Continued study is required to understand the molecular processes that underpin its many effects and to assist its incorporation into evidence-based medicinal applications. It subsequently emphasizes and thoroughly examines G. lucidum's bioactive components, as well as insights into its rising role in healthcare, combining traditional knowledge with recent biological achievements.
Keywords: Anti-tumor activity; Skin health; Ganoderma lucidum; Terpenoids; Fungal immunomodulatory protein; Bioactive molecules